P14 THE IMPACT OF TRANSTHORACIC AND TRANSHIATAL ESOPHAGECTOMY ON LONG-TERM QUALITY OF LIFE ACCORDING TO EORTC QLQ-C30 AND EORTC QLQ-OG25 QUESTIONNAIRES. (23rd November 2019) - Jezerskyte, E; Saadeh, L M; Hagens, E R C; Sprangers, M A G; Noteboom, L; van Laarhoven, H W M; Eshuis, W J; van Berge Henegouwen, M I; Gisbertz, S S
Abstract: Aim: The aim of this study was to evaluate long-term HR-QoL in patients undergoing transhiatal versus transthoracic esophagectomy in a tertiary referral center. Background & Methods: Treatment of esophageal cancers is challenging. Besides (neo)adjuvant chemo(radio)therapy different surgical approaches are possible such as transhiatal (THE) or transthoracic esophagectomy (TTE) with a cervical or intrathoracic anastomosis. Studies have been performed to establish evidence which is the preferred procedure in terms of postoperative morbidity, survival and short- and long-term health-related quality of life (HR-QoL). All patients after THE or TTE for distal esophageal or gastroesophageal junction carcinoma performed between 2003 and 2016 received EORTC QLQ-C30 and EORTC QLQ-OG25 questionnaires. All questionnaires with a follow-up of more than two years after surgery were analysed. Three HR-QoL domains were chosen as primary endpoints: problems with eating, reflux and nausea and vomiting. The secondary endpoints were the remaining HR-QoL domains, postoperative complications and pathology results. The results were corrected for possible confounders such as age and gender. Results: The questionnaire response rate was 47.6%, with 56 patients in the THE group and 134 in the TTE group. The mean age was 63.5 years and a median follow-up of 3.7 years (range 24-137 months) was reached. No significant difference was found in any of the HR-QoL domains or postoperative complications between the two groups. Significantly more lymph nodes were resected in the TTE group (p<0.001). No difference was found in the lymph node metastases or radicality of surgery between the two groups. Conclusion: After a long follow-up of more than two years no differences in HR-QoL or postoperative complications were found between patients with distal esophageal or gastroesophageal junction carcinoma undergoing THE or TTE esophagectomy. Based on this study we conclude that long-term quality of life should not influence the decision making for surgical approach between THE and TTE esophagectomy.